Pola Asuh Orang Tua terhadap Psikis Anak dalam Tiga Cerpen Indonesia - Utami*, Zahwa Febby; Sarifah, Riski Nur (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2024)
The focus of this article is on the parenting pattern depicted in the short story by Leila S. Chudori entitled "Adila", then the short story by Eka Kurniawan entitled “Si Cantik Yang Tak Boleh Keluar Malam”, and the short story by Ratna Indraswari Ibrahim entitled "Anting". Thus, this article will describe (1) the influence of parental parenting; and (2) its influence on the child's psychology. The method used in the research is comparative literature with a qualitative descriptive approach. The primary data source is three short stories. Secondary data sources are library literature. Data collection techniques are listening and taking notes. The data processing technique is document analysis. The results of the research showed that the influence of parenting patterns on children's psychology was found. Children whose lives are under pressure in their families tend to be more silent and determined to do something. Children are also limited in exploring themselves due to the lack of opportunities given.Keywords: child; parenting; psychic Abstrak:Fokus artikel  ini pada pola asuh yang tergambar  dalam cerpen karya Leila S. Chudori yang berjudul “Adila”, lalu cerpen karya Eka Kurniawan dengan judul “Si Cantik Yang Tak Boleh Keluar Malam”, dan cerpen karya Ratna Indraswari Ibrahim berjudul “Anting”. Dengan demikian, artikek  ini akan  mendeskripsikan (1) pengaruh pola asuh orang tua; dan (2) pengaruhnya terhadap psikis anak. Metode yang digunakan dalam penelitian  yaitu sastra bandingan dengan pendekatan deskriptif kualitatif. Sumber data primer adalah tiga buah cerpen. Sumber data sekunder adalah literatur kepustakaan. Teknik pengumpulan data yaitu simak dan catat. Teknik pengolahan data yaitu analisis dokumen. Hasil penelitian menunjukkan ditemukan pengaruh pola asuh terhadap psikis anak. Anak yang hidupnya tertekan di dalam keluarga cenderung lebih diam dan nekat dalam melakukan sesuatu. Anak juga terbatas dalam mengeksplorasi diri akibat minimnya kesempatan yang diberikan.Katakunci: anak; pola asuh;  psikis